Inhibitory effects of total triterpenoids isolated from the Hedyotis diffusa willd on H1975 cells - Wu, Kenan; Wu, Xue; Liang, Yanni; Wang, Ting; Wu, Dongzhi; Li, Luhan; Wang, Zheng (Frontiers in Pharmacology, 2022)
Non-small cell lung cancer (NSCLC), which accounts for more than 80% of lung cancers, is one of the deadly malignant tumors in the world. Currently, it has been discovered that two transcription factors. Nuclear factor-κB (NF-κB) and Signal transducer and activator of transcription 3 (STAT3) were the main factors affecting inflammation and cancer. Hedyotis diffusa Willd. (H. diffusa) is a traditional Chinese medicine, which has always been used for the treatment of malignant tumors. Previous research found that H. diffusa could inhibit the proliferation of H1975 cells, but the specific mechanisms remain elusive. We investigated the effects of total triterpenes saponins extracted from H. diffusa (TSH) on the migration, proliferation and apoptosis of H1975 cells. Cell-cycle and immunofluorescence (IF) analysis showed that TSH could block H1975 cells at G0/G1 phase and induce apoptosis of experimental cells. The protein expression level of Bcl-2 was decreased, while the expression level of Bax was increased. In addition, TSH could also inhibit the migration of H1975 cells through down-regulated MMP-2 and MMP-9 and up-regulated TIMP-2. Further research found that the phosphorylation level of STAT3 was significantly decreased after administration of TSH. And protein expression level of NF-κB in nucleus was decreased after TSH treatment, while NF-κB in cytoplasm increased. These results suggested that TSH could inhibit the proliferation and migration of H1975 cells，and also could induce cell apoptosis. These effects were closely related with the activation of NF-κB and the phosphorylation levels of STAT3.